1977
DOI: 10.1104/pp.59.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Protein Activator of NAD Kinase from Plants

Abstract: Purification of pea (Pisum sativum) seedling NAD kinase by DEAEceilulose column chromatography resulted in loss of activity, due to dissociation of an activator from the enzyme. The purified enzyme preparation, which was almost completely inactive, regained the activity when the activator was added back.The activator was purified 320-fold by ion exchange chromatographies. The (23,24) reported that red light stimulated the conversion of NAD to NADP, and suggested that the NAD kinase activity was controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 23 publications
(15 reference statements)
1
43
0
Order By: Relevance
“…Vertical arrows point to-in "Materials and Methods." Peak 1 is R1T3 (residues 31-37), peak 2 is wards amino termini of trypsin peptides obtained from subdigests of R1T2 (residues [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and peak 3 is RITI (residues 1-13). Composiarginine peptides R I and R5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical arrows point to-in "Materials and Methods." Peak 1 is R1T3 (residues 31-37), peak 2 is wards amino termini of trypsin peptides obtained from subdigests of R1T2 (residues [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and peak 3 is RITI (residues 1-13). Composiarginine peptides R I and R5.…”
Section: Resultsmentioning
confidence: 99%
“…several years ago (1,18) and subsequently calmodulins from spinach (28), barley (22), and peanut (1) have been chemically characterized. The amino acid compositions of plant calmodulins indicate some differences in tyrosine, threonine, leucine, arginine, and lysine content compared to bovine calmodulin.…”
mentioning
confidence: 99%
“…Although a number of reports in the literature have described NADK activity in different plant species (Muto and Miyachi, 1977;Dieter and Marme, 1984;Delumeau et al, 2000;Pou De Crescenzo et al, 2001), evidence of an NADK in Arabidopsis has not previously been reported. Consequently, we examined Arabidopsis extracts for NADK activity.…”
Section: Characterization Of Recombinant and Native Nadk Activity Andmentioning
confidence: 99%
“…Indeed, NADK was the first CaM-regulated enzyme identified in plants (Muto and Miyachi, 1977;Anderson et al, 1980) and remains among the most studied at the biochemical level (Zielinski, 1998). CaM is a ubiquitous and critical Ca 21 sensor found in all eukaryotes where it regulates a diverse array of targets involved in cytoskeletal rearrangements, signaling, metabolism, transcription, and ion homeostasis (Snedden and Fromm, 2001;Yang and Poovaiah, 2003).…”
mentioning
confidence: 99%
“…Calmodulindeficient NAD kinase was partially purified by the method of Anderson et al [18] and calmodulin-dependent activation of the NAD kinase by yeast and bovine calmodulins was determined as described by Muto and Miyachi [17].…”
Section: Preparation and Assay Of Plant N A D Kinasementioning
confidence: 99%